The Tsar, The Empire, and The Nation : Dilemmas of Nationalization in Russia's Western Borderlands, 1905-1915 - Aoshima, Yoko; Staliūnas, Darius (Book collections on Project MUSE., 2021)
"This collection of essays addresses the challenge of modern nationalism to the tsarist Russian Empire. First appearing on the empire's western periphery, this challenge was most prevalent in twelve provinces extending from Ukrainian lands in the south to the Baltic provinces in the north, as well as to the Kingdom of Poland. At issue is whether the late Russian Empire entered World War I as a multiethnic state with many of its age-old mechanisms run by a multiethnic elite, or as a Russian state predominantly managed by ethnic Russians. The tsarist vision of prioritizing loyalty among all subjects over privileging ethnic Russians and discriminating against non-Russians faced a fundamental problem: as soon as the opportunity presented itself, non-Russians would increase their demands and become increasingly separatist"--